Comparison of Microbiological Profiles of Primary Hip and Knee Peri-Prosthetic Joint Infections Treated at Specialist Centers Around the World - Emin Suha Dedeogullari; Pablo Slullitel; Isabel Horton; Bulent Atilla; Saif Salih; Paul Monk; Ahmet Mazhar Tokgozoglu; Michael Goplen; Bonita Tsang; Martin Buljubasich; Hesham Abdelbary; Simon Garceau; et al. (Microorganisms, 2025)
Periprosthetic joint infection (PJI) is a complex complication of total joint arthroplasty, with microbiological profiles varying across centers worldwide. However, most studies are limited to single-center or intra-country multicenter analyses, often including mixed cohorts of primary and revision PJI cases, with limited data regarding global antibiotic resistance patterns. This study compared the microbiological characteristics, polymicrobial culture rates, prevalence of culture-negative infections, and antibiotic resistance patterns in PJI cases across five referral centers from five continents. A total of 717 patients with primary hip and knee PJI were included from centers in Argentina, Canada, Turkey, England, and New Zealand. Staphylococcus aureus and Staphylococcus epidermidis were the most common pathogens (48.5%, p < 0.01). Culture-negative infection rates varied significantly, ranging from 4.2% (England) to 24.6% (Turkey) (p < 0.01). Polymicrobial infections were the most frequent in Canada (8.9%) and the least frequent in England (1.1%) (p < 0.01). Gram-negative bacteria comprised 13.1% of culture-positive cases, with no significant intercountry difference. Multidrug resistance was observed in all centers, ranging from 23.7% (Argentina) to 43.1% (Turkey), with no statistical significance. Vancomycin resistance was detected in England (2.3%) and Canada (1.2%) but absent in Turkey, New Zealand, and Argentina. These findings underscore significant intercontinental variability, emphasizing the need for regional considerations in regards to empiric antibiotic selection and PJI management.